2010
DOI: 10.1002/crat.201000436
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of novel In2O3 nanostructures and their field emission properties

Abstract: Three kinds of novel indium oxide (In 2 O 3 ) nanostructures, namely, nanorods, nanoflowers and nanowhiskers were synthesized on silicon substrate via a simple vapor-phase transport method under atmospheric pressure. The In 2 O 3 nanostructures were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectrometer (EDS) spectrum. The Raman spectra of these nanostructures showed four sharp scattering peaks centered at 308, 365, 522, and 628 cm -1 , whose posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…According to the previous literature, the PL peaks at different wavelengths caused by different subgap energy levels of oxygen defects. , The blue-green (450–490 nm) emission peaks of In 2 O 3 result from the existence of singly ionized V O . ,, The singly ionized V O can serve as donors and induce to form new energy levels in the band gap. The radioactive recombination of the photoexcited hole and the electron occupying V O results in the emission. The stronger blue-green emission peak indicates that there is more singly ionized V O in In 2 O 3 –H10. This result is consistent with the EPR result.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous literature, the PL peaks at different wavelengths caused by different subgap energy levels of oxygen defects. , The blue-green (450–490 nm) emission peaks of In 2 O 3 result from the existence of singly ionized V O . ,, The singly ionized V O can serve as donors and induce to form new energy levels in the band gap. The radioactive recombination of the photoexcited hole and the electron occupying V O results in the emission. The stronger blue-green emission peak indicates that there is more singly ionized V O in In 2 O 3 –H10. This result is consistent with the EPR result.…”
Section: Resultsmentioning
confidence: 99%
“…11,22,47 The reported luminescence peak positions range from 340 nm to 640 nm, which depends on the preparation methods. 9,10,12,16,19,20,25,[47][48][49][50][51] Gan et al employed an electrodeposition method to prepare In 2 O 3 nanocubes deposited on a FTO glass, and observed a strong broad blue emission peak at 405 nm, attributed to singly ionized oxygen vacancies. 2 oxygen vacancies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…16 On the basis of literature, 9,10,12,16,19,20,25,[47][48][49][50] it can be concluded that the luminescence at longer (500-650 nm) wavelengths is due to deep oxygen vacancy energy levels of In 2 O 3 samples prepared by a physical vapor deposition. 16,50 For the In 2 O 3 prepared by a wet chemical method, photoluminescence appears between 400 and 500 nm, consistent with our results. 9,10,12,20,25,[47][48][49] Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trap level emission is enhanced by low crystallinity and structural defects. 45,48,49 In order to compare the luminescence properties of all the photocatalysts, the PL emission spectra of all the photocatalysts are normalised and presented in Fig. S3.…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%